Glomus intraradices improved salt tolerance in Prosopis alba seedlings by improving water use efficiency and shoot water content. - Scambato, Agustina Azul (2011)
The present work was aimed at testing the hypothesis that mycorrhizal Prosopis alba, an economically impor tant tree species worldwide, presents increased salt-tolerance compared with non-mycorrhizal ones and at gaining insight into the possible mechanisms underlying that improvement. For this purpose, a randomized complete block experiment with two factors: mycorrhizal treatments with or without the arbuscular fungus Glomus intraradices and two salinity levels, 0 and 200 mM NaCl was performed. Plant growth in P. alba plants colonized by G. intraradices was less affected by salinity than that in non-arbuscular mycorrhizal (AM) plants, indicating that mycorrhizal colonization turned P. alba more tolerant to salinity. Photosynthesis was reduced by salinity in non-AM plants but not in AM ones.  Salini  ty caused a significant decrease in mean stomatal conductance and transpiration rate, in mycorrhizal plants, but not in uninoculated ones. In this work, we detected two main mechanisms intervening in the salt tolerance enhancement of P. alba by the inoculation with G. intraradices: a- maintaining the net photosynthesis level and b- control of the transpiration rate.  Taken together, the results suggest that inoculation with G. intraradices improves P. alba survival rates during the implantation period and seems to be a promising strategy to improve P. alba cultivation in saline lands.